KIDNEY STONE DISEASE: CAUSES, SYMPTOMS, AND TREATMENT METHODS - Navruzova Ugilkhon Orzijon Kizi; Jumaeva Adolat Buston kizi; Sitora Sadullaeva Jamolovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article provides general information about kidney stone disease. It discusses the causes, symptoms, and treatment methods of the disease. The multifactorial problems of kidney stones are described with indicators, providing more information for treating the disease. It is directed towards individuals receiving medical care related to kidney stone disease.